WEBSITE APPLICATIONS KNOW STATE-COUNTRIES IN USING SOUTHEAST ASIA DREAMWEAVER MX - Sarah Rina Kusumahwati; Irfan. Skom. MMSi Irfan. Skom. MMSi (Jurnal Sistem Informasi, 2007)
Know Your Website Creation Countries in Southeast Asia aims to introduce thecountries in the region of Southeast Asia to their students in elementary school orsecondary.In the manufacture, use Macromedia Dreamweaver MX that starts from the stage ofdetermining the structure of navigation, design page output, exporting to HTMLpages, providing a link in every web page, creation and insertion of animation, webpage processing, as well as how to upload to the web server.With the added animation on every page of the website, making the display moreattractive.